Perbandingan Kadar Vitamin C pada Jeruk Lemon, Jeruk Nipis, Jeruk Purut, dan Jeruk Manis Menggunakan Metode Titrasi Iodimetri - Digna Renny Panduwati; Nova Suci Claudiya Hasibuan (Faculty of Health Science and Technology, University of Jenderal Achmad Yani, 2026)
Background: Background: Citrus fruits are a natural source of vitamin C, which acts as an antioxidant, boosts immunity, supports collagen synthesis, aids in iron absorption, and contributes to wound healing and cellular function. Vitamin C deficiency can lead to scurvy, a condition characterized by symptoms such as fatigue, anemia, bleeding gums, and impaired wound healing. Therefore, analyzing vitamin C levels in food, particularly fruits, is important to determine their contribution to meeting daily nutritional needs. Objective: To determine and compare vitamin C levels in several types of citrus fruits. Methods: The study employed a quantitative approach using the iodometric titration method, known for its simplicity, accuracy, and widespread use in vitamin C analysis. The study samples consisted of four types of citrus fruits: lemon, lime, kaffir lime, and sweet orange. Results: The analysis results showed that vitamin C levels varied among the orange varieties, with the highest value found in lime at 0.08 mg/25g, followed by lemon at 0.06 mg/25g, sweet orange at 0.06 mg/25g, and kaffir lime at 0.05 mg/25g. Conclusion: Variations in vitamin C content are influenced by differences in citrus varieties, ripeness levels, and the characteristics of the soil and growing environment, all of which affect the chemical composition of each fruit.